Enhancement of impact force determination with modal transformation method by using integration and data filtering /Khoo Shin Yee - Khoo, Shin Yee (2013)
Discovering the in-service dynamic forces, their location and their line of action regarding the structure are necessary during its design, development and modification stages. Additional information about the loads experienced by the structure will aid the development iterations resulting in a better outcome. However, direct measurement by using force transducer is not practical in some cases due to some difficulties in force sensor configuration. As an alternative, it would be more convenient to just measure the response and dynamic characteristic of a structure by using Operating Deflection Shape (ODS) analysis and Frequency Response Function (FRF) measurement. Hence, the analysis involved backtracking to determine the force causing the problem can be done. It is known that this inverse problem is ill-conditioned in most practical cases. In this study, a Perspex plate with 4 ground supports was used as test rig. Recovery of unknown impact force using Modal Transformation Method (MTM) is experimentally demonstrated. The transformation from high condition number of synthesised FRF matrix to a well-conditioned case is demonstrated by adding additional information of force location. The low quality of fitting a modal model by using modal parameters obtained from the polynomial curve fitting algorithm is highlighted. In this study, impact force determination with MTM is enhanced by using integration and data filtering approaches. The effectiveness of various types of responses (i.e. measured acceleration responses from sensors; velocity and displacement responses obtained from integration result) is studied, and the results of the impact force determination are examined in under-estimated, even-estimated and over-estimated cases of fixed analysis frequency range. The outcomes show the importance of selecting a suitable response unit and an appropriate analysis frequency range in impact force determination. When the excitation frequency of an impact force is unknown and time-variant, selection of an appropriate analysis frequency range by using Power Spectral Density (PSD) tool is